BARGAINING POWER, ECONOMIC INDEPENDENCE, DECISION MAKING: CASE STUDY OF WOMEN INFORMAL WORKERS THROUGH PHILOSOPHER JOHN STUART MILL - Munte, Alfonso; Monica, Monica (Balai Penelitian dan Pengembangan Agama Makassar, 2023)
The scope of this research is at the level of experience of women informal workers in Pasar Besar Palangka Raya. This experience speaks of bargaining power, empowerment in terms of decision-making, economic independence, body and future authorsity and freedom of expression. Nevertheless, the authors found the imprisonment of double burden in the lives of 3 research subjects. The purpose of this study is to show the extent to which the narrative leads them to live the values of equality through informal work. The research method used is qualitative research with interviews., then the authors recorded, transcribed, made a factual solid and then classified into themes that are close to this research. The results of the research through the experiences of women informal workers in Pasar Besar show that women are found to be empowered over assets, time and in decision-making. On the other hand, both empowerment and imprisonment of women's double burden make John Stuart Mill's philosophical lens dialogue in it when talking about marriage as friendship and not as property or slavery. Mill's intersubjective space becomes a buffer in the narrative of women's experiences of informal workers. In addition, the authors finds that gossiping as a negative stigma by society becomes erroneous when confronted with the daily life practices of women informal workers. Gossip/ngerumpi is able to make women's space a place of self-development, self-protection and self-promotion when women are hit by a flood of fatigue, boredom in terms of waiting for the arrival of buyers.